2021
DOI: 10.1111/1755-6724.13886
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Rock Poroelasticity Evolution in Ultra‐low Permeability Sandstones under Pore Pressure, Confining Pressure, and Temperature: Experiments with Biot's Coefficient

Abstract: This study aimed to show anisotropic poroelasticity evolution in ultra‐low permeability reservoirs under pore pressure, confining pressure, and temperature. Several groups of experiments examining Biot's coefficient under different conditions were carried out. Results showed that Biot's coefficient decreased with increased pore pressure, and the variation trend is linear, but the decreasing rate is variable between materials. Biot's coefficient increased with increased confining pressure; the variation trend i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The structural changes during maturation directly affect the mechanical properties of kerogen, such as microscopic pores and fracture mechanisms, and play a vital role in establishing oil/gas transport channels in shale oil/gas reservoirs. However, kerogen exists at the nanoscale, and the mechanical properties through experiments are challenging to be measured. Therefore, molecular simulation is widely used to the mechanical properties of kerogen.…”
Section: Necessity Of Kerogen Molecular Modelmentioning
confidence: 99%
“…The structural changes during maturation directly affect the mechanical properties of kerogen, such as microscopic pores and fracture mechanisms, and play a vital role in establishing oil/gas transport channels in shale oil/gas reservoirs. However, kerogen exists at the nanoscale, and the mechanical properties through experiments are challenging to be measured. Therefore, molecular simulation is widely used to the mechanical properties of kerogen.…”
Section: Necessity Of Kerogen Molecular Modelmentioning
confidence: 99%
“…The subcritical crack growth rate of the slick water2 group is lower than that of the slick water1 group, because the antiswelling agent added in slick water2 inhibits the osmotic hydration of rock clay minerals. Du et al (2021), observed that the hydration of strong hydrophilic clay minerals in water resulted in very strong surface adsorption reactions, thus could cause an increase in fluid bulk modulus. 24 Therefore, the degree of clay mineral hydration either due to the type of clay mineral or due to environmental conditions could lead to -0.12 -0.08 -0.04 0.00 0.04 0.08 0.12 0.16 0.20 0.24 increased stresses at the crack tip, and hence the observed difference in subcritical crack growth in different environments.…”
Section: Clay Swelling Effect On Subcritical Crack Growthmentioning
confidence: 99%
“…Du et al (2021), observed that the hydration of strong hydrophilic clay minerals in water resulted in very strong surface adsorption reactions, thus could cause an increase in fluid bulk modulus. 24 Therefore, the degree of clay mineral hydration either due to the type of clay mineral or due to environmental conditions could lead to -0.12 -0.08 -0.04 0.00 0.04 0.08 0.12 0.16 0.20 0.24 increased stresses at the crack tip, and hence the observed difference in subcritical crack growth in different environments. About 1.5% more antiswelling agents were added to slick-water group 2 than to group 1 solution.…”
Section: Clay Swelling Effect On Subcritical Crack Growthmentioning
confidence: 99%
“…However, for Chinese continental tight rock reservoirs, the porosity and permeability values are extremely low (porosity is about 10%, permeability is less than 0.3 × 10 −3 µm 2 ), and porosity testing is time-consuming. As a result, the accuracy of the test results decreases, causing logical inversion due to due to inaccurate flowmeter tests [34][35][36][37].…”
Section: The Concept Of "Two-dimensional Permeability"mentioning
confidence: 99%